Forecasting cognitive flexibility through academic resilience in design thinking-enhanced biology lessons - Honra, Joelash R.; Monterola, Sheryl Lyn C. (Intelektual Pustaka Media Utama, 2025)
This study investigates the predictive relationship between academic resilience and cognitive flexibility among students in biology lessons enhanced by design thinking. Using an embedded quasi-experimental design, we compared the effects of design thinking-enhanced lessons with conventional engage, explore, explain, elaborate, evaluate (5E)-based instruction on students' cognitive flexibility and academic resilience. The sample consisted of 97 students divided into experimental and control groups. Pre-test scores were analyzed using descriptive statistics and Levene's tests, confirming initial comparability. The normality of data was verified with the Shapiro-Wilk test. Regression analysis revealed that academic resilience significantly predicts cognitive flexibility, with resilience accounting for approximately 33.7% of the variance in cognitive flexibility. These findings underscore the importance of fostering academic resilience to enhance cognitive flexibility, mainly through innovative teaching methods like design thinking. The implications of this study suggest that integrating design thinking into biology education can effectively develop cognitive and emotional skills, better preparing students for complex problem-solving and adaptive learning. The study contributes to the literature by providing empirical evidence on the role of academic resilience in predicting cognitive flexibility. It offers practical recommendations for educators to incorporate resilience-building activities into their curricula. Further research is recommended to explore additional predictors of cognitive flexibility and their educational implications.